GROWTH PERFORMANCE OF CATFISH (Clarias sp) IN IoT-BASED CULTIVATION - Nurul Fatimah Yunita; Beryaldi Agam; Muhammad Nur Hidayat; Jordi Jordi; Debby Urabi; Sudirman Masara’T; Izhar Amirul Haq; Evelin Agusti (Universitas Mataram, 2026)
One of the widely cultivated aquaculture commodities is catfish (Clarias sp), making it one of the prioritized species for aquaculture development. The development efforts can incorporate IoT technology to control water quality in the culture tanks. Therefore, the aim of this study was to observe the growth performance of catfish (Clarias sp) using an IoT-based water quality control system.This study was conducted for 9 weeks and consisted of two stages. The first stage involved setting up the IoT device system using temperature and TDS sensors, which were then installed in the culture container. The next stage was monitoring growth and water quality. Based on the monitoring results, the average temperature in the culture tank was 27.56 °C and the TDS level was 230 ppm during IoT-based monitoring, with the device accuracy reaching 90%. Growth performance showed an increase in body length of 1.5–2.5 cm per week, with a survival rate of 80%.